2008 OECD 농업분야 논의 대응 : 농업위원회와 농업정책·시장작업반회의를 중심으로 - 송주호 (한국농촌경제연구원, 2008)
Korea has been attending the Committee for Agriculture (CoAg) and its three working parties (APM, JWP on Agriculture and Trade, JWP on Agriculture and Environment) since becoming a member of the OECD in December, 1996. The agendas discussed at the OECD are leading global policy issues of agriculture and could be applied in the policy field usefully. In Korea, however, the government and the academic community have limitations in coping with the OECD discussion due to lack of relevant experts. Therefore, cooperation among the government, academic community, and research institutes is essential. This study analyzes the issues discussed at the sessions of APM (3 times a year) and CoAg (2 times a year). A KREI-OECD workshop was held in Seoul on April 3, 2008 as part of the 30th anniversary of KREI. At the workshop, where 4 OECD representatives took part, PSE, PEM, and Environmental Indicators, the models that analyze agricultural policies of member countries, were reviewed by the participants. Also, a synthesis report titled “Agricultural Policy Design and Implementation” was presented by the OECD representatives. In other sessions, Korea and the OECD representatives exchanged views on the ‘Evaluation of Agricultural Policy Reforms in Korea.' At the 150th OECD Committee for Agriculture (13-15 May, 2008), discussions were held on the main agendas of ‘2009-2010 PWB,' ‘Economic Assessment of Biofuel Support Policies,' ‘Agriculture and the Environment,' and the schedule of GFA. The document titled ‘In-Depth Evaluation of the CoAg’ reported that the Committee's operations were evaluated ‘average’ in the areas of relevance and efficiency and ‘high’ in the area of effectiveness. One of the main issues discussed at the following 151st CoAg (18-19 Nov., 2008) concerned the Committee's administrative operations like follow-up recommendations of an in-depth evaluation of CoAg and a review of the committee’s sub-structure. Decisions were also made to integrate the two commodity groups of the APM into the ‘Group on Commodity Market’ and to determine the date of a symposium to be held on what implications globalization might have on the food market and public policy. Also, a survey of participating delegates to the 151st Committee Meeting was conducted to find out about their preferences for the themes to be discussed at the 2010 Ministerial Meeting. At the 45th APM (19-20 Feb., 2008), an OECD report titled “Evaluation of Agricultural Policy Reforms in Korea” was published. The report assessed the achievement of agricultural policy reform in Korea and advised additional measures for more market-oriented agriculture. A synthesis report on agricultural policy design and implementation was also published. It described policy principles behind the successful reforming of decoupling, targeting, and farm income issues. The other agendas discussed at the meeting were “The Role of Farm Households and the Agro-Food Sector in the Economies of Rural Areas,” “Risk Management in Agriculture,” and “Recommendations of PSE Expert Group.” At the 46th APM (20-21 May, 2008), the OECD-FAO Agriculture Outlook 2008-2017, which forecast the supply, demand and price of grains, was presented. According to Monitoring and Evaluation, the producer support estimate (PSE) for 2007 was shown to be at 23%, the lowest level ever. Also, the delegates examined ‘the interaction of public and private standards in the food chain’ and ‘the evaluation of agricultural policy reforms in Japan.’ At the 47th APM (13-15 Oct., 2008), the delegates pointed out that the document “The Role of Farm Households and Agro-Food Sector in the Economy of Rural Areas: Evidence and Policy Implications” overstated the influence of technical change. They discussed the state of affairs related to the creation of new values and the government's role in the agro-food sector. Member countries asked the Secretariat to prepare the document in a way that analysis results can present policy implications. In the discussion of ‘coverage and measurement of transfers of water in the PSE and GSSE calculations,’ the delegates confirmed the principle that PSEs are calculated based only on the amount of water that is actually supplied to farmers. Discussions were held on the document ‘Policy Initiative Concerning Diet, Health and Nutrition,' but the delegates decided to shelve the idea of declassifying it after they reviewed the document ‘Risk Management in Agriculture?a Holistic Conceptual Framework.’ Researchers: JooHo Song, HoGun Jung, HyungHyun Yoon Research period: 2008. 3-12 E-mail address: jhsong@krei.re.kr